(untitled) (Bangladesh Journal of Infectious Diseases, 2026)
Background: Cancer continues to be one of the leading causes of worldwide mortality, which has led to a quest for new therapeutic agents, including natural products from plants. Moringa oleifera is a medicinal plant, and TRAIL shows an affinity to apoptosis in cancer cells. Objective: The purpose of the present study was to evaluate the individual and combined effects of an ethanolic extract of Moringa oleifera seeds and the chemotherapeutic agent docetaxel on the viability and TRAIL expression of the LNCaP human prostate cancer cell line. Methodology: Ethanolic extract was obtained from the seeds of Moringa oleifera by Soxhlet’s apparatus. LNCaP cells were then exposed to different doses of extract, docetaxel and/or the combination. MTT assay detected cell viability after 24 and 48 h. The levels of TRAIL were measured with an ELISA kit. Results: The Moringa oleifera seed extract and docetaxel significantly induced dose- and time-dependent reductions in LNCaP cell viability (P ≤ 0.001) along with significant increases in TRAIL levels. The IC 25 of the extract in combination with IC 50 dose of docetaxel exhibited synergistic potentiation of antiproliferative activity, accompanied by a highly remarkable enhancement in TRAIL expression (P ≤ 0.001). Conclusion: Moringa oleifera seeds ethanolic extract has a potent antiproliferative and pro-apoptotic activity in LNCaP cells, which is partly mediated through TRAIL up-regulation. In addition, it has a synergistic effect with docetaxel and can be used as an adjuvant therapy for prostate cancer. Bangladesh Journal of Infectious Diseases, December 2025; 12(2):222-227